A Comprehensive Survey on Methods Implemented For Intruder Detection System - Kiranmai, B; Damodaram, A (International Journal of Computer Sciences and Engineering, 2014)
Intrusion recognition is the act of discovering undesirable visitors on a system or a system. An IDS can be a piece of set up software or a physical equipment that watches system visitors in order to identify undesirable action and activities such as unlawful and harmful visitors, visitors that goes against security plan, and visitors that goes against appropriate use policies. Intruder detection system can be implemented using various data mining approaches. This paper summarizes intrusion motives and some of the methods used and implemented for intrusion detection system. This paper also reviewed about processing environment and type of data required for evaluation of Intruder detection system.